2′-Hydroxychalcone Induced Cytotoxicity via Oxidative Stress in the Lipid-Loaded Hepg2 Cells - Qian, Yun; Yang, Yang; Wang, Kai; Zhou, Wenjun; Dang, Yanqi; Zhu, Mingzhe; Li, Fenghua; Ji, Guang (Frontiers in Pharmacology, 2019)
Licorice is a common herb used in traditional Chinese medicine, and has been widely used clinically. Physiologically although it is relatively safe, licorice-induced hepatotoxicity in the presence of other diseases needs to be evaluated. The present study was conducted to investigate the toxicological effects of the bioactive components of licorice in HepG2 cells cultured with or without free fatty acid (FFA). The compounds, isoliquiritigenin, licorice chalcone A, bavachalcone, and 2’-hydroxy chalcone (2’-HC) inhibited cell proliferation at certain concentrations in lipid loaded cells with limited effects on the normal cells. The representative compound 2’-HC (at a concentration of ≥ 20μM) increased the oxygen consumption rate, ATP production, mitochondrial membrane potential, generation of total and mitochondrial reactive oxygen species (ROS) production, and expression of inflammatory cytokines (TNF-α, IL-6, and IL-8) and Caspase-9 protein; and reduced the expression of SOD1. In addition, we found exaggerated lipid accumulation in HepG2 cells treated with FFA. Our results suggest that 2’-HC at a concentration of ≥ 20μM might cause damage to the hepatocytes. The toxicity may be related to excess ROS production and inadequate SOD1 expression, leading to apoptosis, inflammation, and cellular dysfunctions.